A study on wettability properties of rutile-phase TiO2 nanostructure film - Taib, Syafa Syahirah (2020)
Titanium dioxide (TiO2) is a very well-known material for applications such as photocatalysis, solar cell and self-cleaning applications. This material can also be coated on glass surfaces, especially for car windows and building windows as well. Glass in the market nowadays, the material that coated on the glass weakens as time passes and harmful to the environment. Since TiO2 material has advantages such as being inert and environmentally friendly, thus the study of the wettability properties of rutile-phase TiO2 film is introduced for self-cleaning application. TiO2 is fabricated using the hydrothermal synthesis method at 150°C. The fluorine-doped tin oxide (FTO) is used as a substrate to grow the TiO2 nanostructure by mixing hydrochloric acid (HCl), deionised water (DI) and titanium (IV) butoxide (TBOT). The effects of the duration of the hydrothermal process, the volume of HCl, the volume of TBOT as well as the use of surfactant hexadecyltrimethylammonium bromide (HTAB) toward the synthesis growth of nanorods are thoroughly evaluated. The samples are analysed by using X-Ray Diffraction (XRD) for structural properties, Field Emission Scanning Electron Microscopy (FE-SEM) for morphology structure and water contact angle (WCA) measurement for wettability properties. FE-SEM shows that the layer of TiO2 nanorods is successfully grown on the FTO substrate. The contact angle results for different hydrothermal reaction times and different HCl and TBOT volumes reveal that TiO2 has wettability properties of hydrophilicity (<90°). Even though different structures are achieved from different parameters, none of the samples exhibit hydrophobic characteristics. From the XRD data analysis, all of the samples are rutilephase TiO2. The optimum amount of hydrothermal reaction time, volume of HCl and volume of TBOT are at 16 hours, 130 mL and 5 mL, respectively, where TiO2 has a crystalline structure with fine tetragonal shape and the highest contact angle. The use of HTAB have a change in wettability properties as it makes the sample become superhydrophilic compared to as-prepared sample which is hydrophilic only.